Cardiovascular Autonomic Regulation and Performance Anxiety in Athletes: A Narrative Review - Strumińska, Julia; Nowosielska-Ogórek, Agnieszka; Śmigielska, Maja; Janczak, Sylwia; Węgrzyn, Tymoteusz (Quality in Sport, 2026)
Background Performance anxiety is a well-documented phenomenon in competitive sport with established behavioural and psychological consequences; however, its physiological correlates - particularly with respect to cardiovascular autonomic regulation - remain insufficiently integrated within sport medicine and cardiology literature. Objectives This narrative review aims to synthesize current evidence on the relationship between performance anxiety and cardiovascular autonomic function in athletes, with particular emphasis on heart rate variability (HRV) as a non-invasive biomarker of autonomic balance. Methods A structured literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar, including studies published from 1996 to 2026, with selected seminal works published prior to this period. Eligible sources comprised original research articles, systematic reviews, meta-analyses, and clinical guidelines addressing heart rate variability, performance anxiety, and autonomic nervous system regulation in athlets. Results Converging evidence indicates that elevated anxiety is associated with reduced HRV, reflecting sympathetic dominance and reduced parasympathetic activity. This imbalance may negatively affect athletic performance, recovery, and cardiovascular health. Activation of the hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS) appears to link psychological stress with physiological dysregulation. Conclusions Performance anxiety may contribute to autonomic imbalance characterized by sympathetic dominance and reduced HRV, leading to impaired performance and recovery. These findings support the use of psychophysiological monitoring and targeted psychological interventions in athlete health management.